Peran Pendidikan Ketarunaan dalam Mengatasi Kenakalan Remaja - Annisah Annisah; Nur ‘Afifah (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2022)
Juvenile delinquency requires handling from various sides, including schools in the form of character education. Ketarunaan system has proven to be effective in character building. Purpose of this research is to describe the role of ketarunaan system that is implemented at SMKN 61 Jakarta for overcoming juvenile delinquency. Research approach which is used for this research is qualitative approach and it was conducted from January-July 2020. The data is collected by interview and observation of taruna/taruni, schools, and taruna-taruni parents. Informants from taruna-taruni are students who have juvenile delinquency history in the heavy category; from various grade of class and who shown a change. Data analysis was carried out by open, axial, and selective coding. Result of the research shows that Ketarunaan system consist of 3 development models: intrakurikuler, ko-kurikuler, and ekstrakurikuler. Three development models form discipline character, independence, and responsible in taruna-taruni. The density of their activities makes them reduce their free time to do negative activities. The number of delinquency which is committed by taruna/taruni is significantly reduced. It was concluded that ketarunaan system which is implemented by SMKN 61 Jakarta was effective in overcoming the problem of juvenile delinquency.